2010
DOI: 10.1111/j.1600-0463.2009.02574.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of invasive protein profile of Streptococcus pyogenes M1 isolates from pharyngitis patients

Abstract: Streptococcal toxic shock syndrome (STSS) is a re-emerging infectious disease in Japan and many other developed countries. Epidemiological studies have revealed that the M1 serotype of Streptococcus pyogenes is the most dominant causative isolate of STSS. Recent characterization of M1 isolates revealed that the mutation of covS, one of the two-component regulatory systems, plays an important role in STSS by altering protein expression. We analyzed the M1 S. pyogenes clinical isolates before or after 1990 in Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
39
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 49 publications
3
39
0
Order By: Relevance
“…The S. pyogenes strains used in this study were SF370 (Ferretti et al, 2001) and the 1529 clinical isolate from a Japanese patient with STSS. As far as CovS is concerned, comparison of the covS sequence with that of SF370 indicated that the mutation in 1529 is the same as the one previously reported [994(AAG), relative to the covS start site, amino acid change IAV] (Sumby et al, 2005;Hasegawa et al, 2010b).…”
Section: Methodssupporting
confidence: 69%
“…The S. pyogenes strains used in this study were SF370 (Ferretti et al, 2001) and the 1529 clinical isolate from a Japanese patient with STSS. As far as CovS is concerned, comparison of the covS sequence with that of SF370 indicated that the mutation in 1529 is the same as the one previously reported [994(AAG), relative to the covS start site, amino acid change IAV] (Sumby et al, 2005;Hasegawa et al, 2010b).…”
Section: Methodssupporting
confidence: 69%
“…Streptococcal strains 1529, MDYK, and MDN were isolated from Japanese patients with STSS [21,22]. S. pyogenes (GAS) strain SF370, which is currently the most prevalent database reference isolate (accession number NC_002737), was provided by J. J. Ferretti [23,24].…”
Section: Methodsmentioning
confidence: 99%
“…Engleberg et al [15] showed that most covS mutations were frameshift or nonsense mutations in isolates from mice infected with the M1 strain. In contrast, all of the spontaneous changes in CovS detected in clinical M1 isolates [22] resulted from single amino acid substitutions. Thus, we were interested in why this difference occurred and we hypothesized that it was related to the use of animal-passaged isolates in the first study whereas the latter used clinical isolates.…”
Section: Introductionmentioning
confidence: 99%